Sense and Reality. Essays out of Swansea - Edelman, John (Publications of the Austrian Ludwig Wittgenstein Society - New Series (N.S.), 2009)
This book is a collection of essays each of which discusses the work of one of eight individuals - Rush Rhees, Peter Winch, R. F. Holland, J. R. Jones, H. O. Mounce, D. Z. Phillips, Ilham Dilman and R.W. Beardsmore - who taught philosophy at the University of Wales, Swansea, for some time from the 1950s through to the 1990s and so contributed to what in some circles came to be known as 'the Swansea School'. These eight essays are in turn followed by a ninth that, drawing on the previous eight, offers something of a critical overview of philosophy at Swansea during that same period. The essays are not primarily historical in character. Instead they aim at both the critical assessment and the continuation of the sort of philosophical work that during those years came to be especially associated with philosophy at Swansea, work that is deeply indebted to the philosophy of Ludwig Wittgenstein but also distinctively sensitive to the relevance of literary works to philosophical reflection.